Towards Inclusive AI: A Theoretical Exploration of Sociolinguistic Variations and Biases in NLP Models - Manzar Shahbaz; Saqlain Mushtaq (Indus Journal of Social Sciences, 2025)
To improve the interaction between humans and machines, the integration of sociolinguistic concepts into artificial intelligence (AI) systems marks a significant step forward. Sociolinguistics studies how social factors like culture, identity and context shape language thus providing essential understandings for addressing the linguistic and cultural diversity among global AI users. This paper explores the theoretical aspects of how sociolinguistics influences AI communication, emphasizing how concepts such as linguistic variation, pragmatic competence, and conversational context can help create more adaptable and inclusive AI systems. The analysis starts by placing AI’s increasing role in daily communication into context, pinpointing shortcomings in current models that struggle to replicate sociolinguistic behaviors like accommodating regional dialects, managing code-switching, and understanding indirect speech acts. The paper investigates the challenges that Artificial intelligence (AI) faces in representation of marginalized linguistic communities and also addresses biases present in training dataset by drawing on foundational sociolinguistic theories from Labov (2006) and Gumperz (1982), along with advancements in natural language processing (NLP). The study points out specific areas where insights from sociolinguistics can enhance AI design, for example managing linguistic diversity, understanding pragmatic nuances, and facilitating cross-cultural communication. It also considers ethical issues like fairness and inclusivity in AI training and deployment. This research aims to advance both theoretical understanding and practical applications in human-machine interaction by proposing a conceptual framework that incorporates sociolinguistic principles into Artificial Intelligence (AI).